Implementation of Quranic-Based Communication to Improve Harmonious Relationships between Teachers and Students in Islamic Religious Education - Zakiyah BZ, Zakiyah BZ; Maulani, Alda (Universitas Pahlawan Tuanku Tambusai, 2025)
The main focus of this study lies in the implementation of Qur'anic-based communication in improving harmonious relationships between teachers and students at SMA Nurul Jadid, especially in Islamic Religious Education (IRE) subjects. The purpose of this study is to analyze how the implementation of Qur'anic-based communication can strengthen interpersonal relationships between teachers and students in the context of learning. The method used in this study is qualitative with a case study design. The results of the study indicate that the implementation of Qur'anic-based communication, which includes qaulan layyinan (gentle words), qaulan kariman (noble words), and qaulan maysuran (easy-to-understand words), has a positive impact on teacher-student interactions. Teachers who use gentle language and respect students are able to create a more comfortable and conducive classroom environment. This increases students' confidence in actively participating in discussions, reduces anxiety in expressing opinions, and facilitates understanding of teaching materials. In addition, this study found that Qur'anic communication contributes to overcoming differences in understanding among students by providing a more inclusive and empathetic approach. By applying easy-to-understand language and gradually explaining the material, teachers can help students who have difficulty understanding Islamic teachings without creating pressure or fear. The implications of this study indicate that Qur'anic-based communication can be an effective strategy in creating better interpersonal relationships in educational environments. The application of Islamic communication principles not only improves the quality of learning but also contributes to the world of education by presenting communication techniques that are oriented towards empathy, respect for students, and strong religious values.